Metabolic Syndrome in Commercial Truck Drivers: Prevalence, Associated Factors, and Comparison With the General Population. Issue 7 (July 2020) - Robbins, Riann B.; Thiese, Matthew S.; Ott, Ulrike; Wood, Eric M.; Effiong, Atim; Murtaugh, Maureen; Kapellusch, Jay; Cheng, Melissa; Hegmann, Kurt
Abstract : Introduction: Commercial motor vehicle drivers, such as truck drivers, experience unique health, lifestyle, and occupational challenges directly associated with their profession. Methods: All participants in this multistate cross-sectional study completed questionnaire measurements. Participants were categorized with metabolic syndrome (MetS) if they had at least three of the five modified criteria used in the joint scientific statement on metabolic syndrome. Results: Overall MetS prevalence was 52.4% ( n  = 428) of the 817 participants. Prevalence of MetS criteria were waist circumference ( n  = 634, 77.0%), low HDL cholesterol ( n  = 580, 71.0%), elevated triglycerides ( n  = 552, 67.6%), elevated blood pressure ( n  = 175, 21.2%), and elevated hemoglobin A1c ( n  = 97, 11.9%). Truck drivers were 2.7 times more likely to have MetS compared to the general working population. Conclusion: Truck drivers in the United States have a high prevalence of MetS compared to the general working population.